Towards sustainable multi-bed hospital wards: numerical evaluation of infection control, thermal comfort, and energy savings under real-world ventilation strategies - Mei Yan Chong; Hui An; Brenda Sze Peng Ang; Chew Beng Soh; Szu-Cheng Chien; Peng Cheng Wang; Simon Ching Man Yu (Energy and Buildings, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Akkermansia muciniphila: promises and pitfallsfor next-generation beneficial microorganisms - Yantong Liu; Zonglun Li; Sze Ching Lee; Shurui Chen; Feifei Li (Archives of Microbiology, 2025)

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Model validation and applications of wave and current forecasts from the Hong Kong Observatory's Operational Marine Forecasting System - Wai Kong; Ching-chi Lam; Dick-shum Lau; Chi-kin Chow; Sze-ning Chong; Pak-wai Chan; Ngo-ching Leung (Ocean Modelling, 2024)

Characterization of size-differentiated airborne particulate matter collected from indoor environments of childcare facilities - Gayatri Sankaran; Sze Tat Tan; Rowena Yap; Mei Ling Chua; Lee Ching Ng; Saji George (Chemosphere, 2023)

Size-tunable Sargassum polycystum mediated synthesis of silver nanoparticles and its larvicidal effect on Aedes aegypti - Jo Sze Lean; Wan Najdah Wan Mohamad Ali; Rohani Ahmad; Zurainee Mohamed Nor; Ching Lee Wong; Jeck Fei Ng (Journal of Applied Phycology, 2023)

Assessment of indoor air quality in air-conditioned small business units with no mechanical ventilation - Gayatri Sankaran; Sze Tat Tan; Joanna Shen; Ramona Gutiérrez; Lee Ching Ng; Shuzhen Sim (Atmospheric Environment, 2023)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)